The Interaction in Education in Broad Sense - Montvilaitė, Sigita (Acta Paedagogica Vilnensia, 2000)
The pedagogical process develops in compliance with the general laws the most important of which is the law of interaction. The success of education in its broad sense depends upon the character of communication between the educator and the pupil. The education is deemed successful if the interaction between the educator and the pupil acquires the form of communication, if it is based on partnership and equality, on mutual respect and trust. This problem has already been mentioned by J. Vabalas-Gudaitis, the famous Lithuanian educator of the pre-war period. In his pedagogical and psychological articles, J. Vabalas-Gudaitis emphasized the importance of democratic communication as a precondition for education of an independent, initiative, active, responsible, respectful and respectable person.